Neurocognitive markers following coronary artery bypass grafting with and without cardiopulmonary bypass - Rahman, A; Yoldas, T; Ustundag, B; Burma, O; Uysal, A; Cikim, G; Donder, E (Medimond S R L, 2001)
Neurocognitive dysfunction constitute the leading cause of morbidity and disability after cardiac operation. The aim of this study was to measure the effects of coronary artery bypass grafting (CABG) with and without cardiopulmonary bypass (CPB) on neurocognitive fuction. Thirty patients (n:30) were randomized to receive CABG either with (group 1, n:15) or without (group 2, n:15) CPB. Event related potentials (ERPs) were stuided and latency of the P300 component was measured preoperatively and postoperative 5th day. Serum neuron specific enolase (NSE) levels were measured preoperatively, postoperative 1st, 3rd and 5th days. Postoperative prolongation of P300 ERPs was more severe in the group 1 (from 342 to 381 ms) as compared to the group 2 (from 346 to 359 ms,) (p<0.05). Preoperative NSE levels were similar in both groups. Patients in the group I had significantly higher NSE levels than patients in the group 2 at postoperative 1st day (31.6 versus 15.6 (mug/L, p<0.001), 3rd day (25.9 versus 14.0 mug/L, p<0.001) and 5th day (16.4 versus 8.3 mug/L, p<0.001). Based on cognitive ERPs (P300) and serum NSE measurements, CABG without CPB, potentially led to significantly lower cognitive brain injury than CABG with CPB. This may be due to avoiding the inflammatory response, microembolic events, and hypothermia related to CPB.
4th International Congress on Coronary Artery Disease -- OCT 21-24, 2001 -- PRAGUE, CZECH REPUBLIC
Keywords: Cardiac-Surgery